The Bloomsbury handbook of gender and educational leadership and management - Moorosi, Pontso; Oplatka, Izhar; Shakeshaft, Charol; Showunmi, Victoria (Bloomsbury Handbooks, 2022)
"Drawing together diverse research perspectives and theoretical underpinnings, this handbook explores gender as a social category and examines cultural and social differences. Bringing together diverse perspectives from around the world, including from Africa, Europe, the Middle East, the UK and the USA, the volume sets out the gender and educational leadership and management field, providing a snapshot of the field as it stands, signalling its development and directions for future development. It offers focused reviews of empirical research on particular aspects of the field and presents new insights from research findings and methodological approaches"--Provided by publisher.